Landslide disaster mitigation in Sawahlunto City - Haqia Purnama Tirza; Ekha Putera Roni; Koeswara Hendri (E3S Web of Conferences)
The research aims to analyze the implementation of landslide disaster mitigation in Sawahlunto. Motivated by the high risk of landslides in Sawahlunto. Efforts are needed to reduce the risk of landslides by implementing the theory used of W.N. Carter’s theory of non-structural and structural disaster mitigation. The method used is descriptive qualitative, with data collection techniques using interviews, documentation, and observation. This is concluded that the implementation of landslide disaster mitigation in Sawahlunto has been running, but the implementation has not been optimal. Several things, non-structural, cause this: In the legal framework, a lack of understanding of policies that contain appropriate mitigation as well as the role of each agency or institution; the disaster risk reduction forum (FPRB) has been formed at the level, but at the village level only has a disaster preparedness group (KSB); the lack of implementation of disaster mitigation measures by the community. Structural disaster mitigation activities are still inadequate, as seen from the unavailability of vertical evacuation buildings. Efforts that can be made to support the implementation of landslide disaster mitigation in Sawahlunto include reviewing mitigation policy documents, increasing the capacity of FPRB, and collaborating with various parties to support the implementation of disaster mitigation.